Analisis keausan slewing gear 242-UB1 area unit ship unloader PT Solusi Bangun Indonesia Tbk - Fikry Alvianto Kurniawan, Fikry; Kurniawan, Stephanus Danny; Handoko; Prihadianto, Braam Delfian (Jurnal Teknik Mesin Indonesia, 2024)
Ship Unloader is a unit of equipment to move materials from marine units to other units related to the production process by performing travel movements by slewing gear components. The problem of damage in the slewing gear began after inspecting and replacing components. The gear tooth on the slewing gear experiences abnormal wear. This study aims to analyze the wear of the slewing gear component 242-UB1 in the Ship Unloader unit area at PT Solusi Bangun Indonesia Tbk. The research methods are field surveys, data collection, and fishbone diagrams. Research materials and tools include dial indicator, filler gauge, lead wire, slewing gear components, and vernier calliper. Data was obtained from monitoring the unit and equipment with RCA analysis. The analysis showed that backlash was a significant contributing factor to wear with the worst value of 2.0 mm. In addition, the percentage of wear on the top gear reached 25%, which means it has reached the red zone limit. How to reduce potential wear due to backlash by regular monitoring of the backlash gap online through sensors. In conclusion, the study revealed that component wear is closely related to the backlash phenomenon. In addressing this issue, regular monitoring, timely repairs, and selection of appropriate materials and lubricants are considered as measures that can reduce wear potential and increase component life.